Investigating friction stir welding on thick nylon 6 plates - Zafar, A. (American Welding Society, 2016)
Polymeric materials, despite being thermal insulators, are now being welded using different welding techniques. In the current work, the feasibility of the friction stir welding (FSW) process on 16-mm-thick Nylon 6 plates was studied. The effects of rotational speed on the weld quality were investigated by the temperature development, micro-mechanical properties, crystallization growth, and fracture analysis of the joints. Results showed the dependence of temperature and tensile values on rotation rates was insignificant. However, appearance of considerable defects at higher rotation rates, observed in visual and microscopic analysis, indicated that Nylon 6 is weldable only at lower rotation rates due to its low melt viscosity. Moreover, identical fracture locations during tensile tests revealed that the interface of weld zone on the retreating side was the weakest part of the joint. It can be attributed to the lack of bonding at the interface of the weld zone on retreating side and relatively low crystallinity in the retreating side region. Due to different rheological and physical properties of polymers than metals, the flow phenomenon in Nylon 6 was found to be different from that of metals, resulting in a distinct isolated pin plunged zone.